ANALYSIS OF THE EFFECTIVENESS OF SOCIAL MEDIA INSTAGRAM AS A PROMOTIONAL PLATFORM OF NHU NHU LEMONGRASS PRODUCTS: English - Nanda Trisna Prihartini; Mubarokah Mubarokah; Ika Sari Tondang (Yayasan Education and Social Center, 2023)
The trend of popular drinks has been growing over the past few years. In the face of high competition and large market opportunities, Nhu Nhu Lemongrass uses Instagram as the main media for promoting its products. The result of this study is that the promotional activities of Nhu Nhu Lemongrass are in the good enough category. While alternative actions for improving the promotion of Nhu Nhu Lemongrass on Instagram can be done by utilizing Instagram's paid advertising features, designing informative promotional content, and increasing interaction with target consumers